Mapping of the depth of hard/dense layer at Banda Aceh-Indonesia and the surrounding areas. Issue 1 (February 2021) - Yunita, H; Al-Huda, N; Saidi, T; Sundary, D; Gunawan, H; Yulianur, A; Setiawan, B; Adrian, F; Sartika, D; Oucherif, M S
Abstract: The 26 December 2004 disaster caused enormous casualties and damages in affected regions. Indonesia suffered a loss of 42.7 trillion Rupiah. On the other hand, this disaster has raised awareness among some people to carry out construction following engineering principles, so that the newly constructed buildings have an adequate level of safety. A hard/dense soil layer has a close relationship with the safety level of a building. This paper proposes a map of the depth of hard/dense (stable) layer at one of the worst affected cities, i.e., Banda Aceh (Indonesia) of the boxing day 2004 disaster. A static cone penetration test (CPT) was employed to determine the depth of stable soil. The data from the 35 cone penetration tests were used to develop the zoning map of the depth of the stable soil in the study location. The dominant hard/dense soil depth in the study location is > 10 meters below the existing ground level. In certain places, such as the areas around Lambung, Neusu Aceh, Lambaro Skep, Jeulingke, Doi, Kopelma Darussalam, and Lamjame, the depth of stable soil is from 5 to 10 meters.